Mechanical properties of 18 different AO bone plates and the clamp-rod internal fixation system tested on a gap model construct - Zahn, K.; Frei, R.; Wunderle, D.; Linke, B.; Schwieger, K.; Guerguiev, B.; Pohler, O.; Matis, U. (Veterinary and Comparative Orthopaedics and Traumatology, 2008)
Objective: To compare the stiffness and strength of AO bone plates (DCP, LC-DCP, VCP, RCP, and LP) and the Clamp-Rod Internal Fixation System (CRIF). Study design: In vitro. Sample size: 12 individual implants of 18 plate dimensions and four sizes of CRIF, each corresponding to 2.0, 2.4/2.7, 3.5, or 4.5 mm screw sizes. Methods: Implant-constructs of each plate and CRIF were created using Canevasit rods as a bone substitute in an unstable gap fracture model. Six implantconstructs of each type were tested under single cycle four-point bending loading, and six were tested under single cycle torsional loading until permanent plastic deformation occurred. Results: Torsional stiffness and yield load of the DCP were always significantly greater than the CRIF within the same group. Bending properties of the 2.0 DCP were not significantly different to the 2.0 CRIF. The 2.7 DCP had significantly higher bending values than the 2.7 CRIF. The bending stiffness of the 3.5 DCP and 4.5 DCP was significantly less than their CRIF counterparts. While the bending yield load of the 3.5 DCP was significantly greater than the 3.5 CRIF, the bending yield load of the 4.5 DCP was significantly less than the 4.5 CRIF. Conclusion: A weakness was found in the torsional resistance of the CRIF constructs compared to the DCP constructs. Clinical significance: Bone holding power and applied screw torque should be considered when using the CRIF system in clinical application.
Keywords: Plates; CRIF; stiffness; strength; Mechanical testing